Enhancing Interior Design Education: The Role of the King Salman Urban Charter in Cultural Heritage Understanding (The International Journal of Educational Sciences and Arts, 2025)
Cultural heritage transcends mere material legacy from the past, serving as a crucial component that reflects a society's identity and cultural values. Educational institutions, particularly in the fields of interior architecture and design, play a pivotal role in cultivating this understanding among future generations. However, challenges such as inadequate integration of theoretical and practical aspects in teaching cultural heritage concepts can diminish students' awareness of their significance and application in professional contexts.This study aims to investigate the impact of varied educational methods on enhancing interior design students’ comprehension of architectural and cultural heritage concepts. It also evaluates the effectiveness of these methods in conveying values and knowledge supportive of cultural identity preservation. The findings of this research hold practical implications for educators in the field of interior design, providing insights into effective strategies for teaching cultural heritage concepts.A sample comprising third-level female students from the Department of Interior Design at Taif University (n=55) was selected. The authors employed a classic experimental design framework, facilitating comparison between experimental and control groups via pre- and post-measurements. A two-hour experimental workshop was conducted to introduce the King Salman Urban Charter for Architecture and Urbanism through two distinct methodologies: one that utilized an experimental approach incorporating brainstorming, practical education, and technology, specifically artificial intelligence; and the other that adopted a traditional lecture-based approach.The findings revealed that the effective teaching strategy for architecture and design involves combining traditional lectures, which enhance knowledge and understanding, with experimental methods that promote creativity and engagement. This integrated approach significantly improves students' comprehension and application of cultural heritage concepts.
Keywords: King Salman Urban Charter for Architecture and Urbanism; Cultural heritage; Educational methods; Artificial intelligence